Peningkatkan Kebiasaan Bertanya Siswa Melalui Layanan Bimbingan Kelompok pada Siswa - Kusri Andi Muhammad (KONSELING: Jurnal Ilmiah Penelitian dan Penerapannya, 2021)
This research is to improve the habit of asking students by optimizing group guidance services. This research was conducted at SMPN 2 Unggulan Maros. The subjects of this study were class VIII students. There were 10 students. The procedure of this research consists of planning, action, observation and reflection. This action research consists of 3 cycles, each cycle is carried out with a different topic, cycle 1 uses free topics, cycle 2 uses assignment topics, and cycle 3 uses mixed topics, namely free topics and assignments. This research technique uses observation and questionnaire techniques, data collection tools are observation instruments and questionnaire instruments. Data analysis in this study used descriptive qualitative consisting of data processing, data analysis, and data presentation. The results of this study indicate that there is an increase in students' habit of asking questions through optimizing group guidance services. The habit of asking questions can be seen from the results of observations during the action process in group activities, namely an increase in asking questions, the form of behavior displayed is spontaneous, choosing the right time to ask questions and asking well without other people's problems. As supporting data to find out the increase in the habit of asking questions is through observations made by BK teachers and subject teachers as comparisons. The result is that there is an increase in the habit of asking questions in the learning process gradually from cycles 1, 2 and 3. In cycle 1. The frequency of asking is 40%, the second cycle is 60% and in the third cycle there is 80%. Thus, through optimizing group guidance services, it is possible to increase the activeness of asking group members in the learning process.